Clonal Spread and Intra- and Inter-Species Plasmid Dissemination Associated With Klebsiella pneumoniae Carbapenemase-Producing Enterobacterales During a Hospital Outbreak in Barcelona, Spain - Marí-Almirall, Marta; Ferrando, Núria; Fernández, Mariana José; Cosgaya, Clara; Viñes, Joaquim; Rubio, Elisa; Cuscó, Anna; Muñoz, Laura; Pellice, Martina; Vergara, Andrea; Campo, Irene; Rodríguez-Serna, Laura; et al. (Frontiers in Microbiology, 2021)
Objectives: The study aimed to characterize the clonal spread of resistant bacteria and dissemination of resistance plasmids among carbapenem-resistant Enterobacterales at a tertiary hospital in Catalonia, Spain. Methods: Isolates were recovered from surveillance rectal swabs and diagnostic samples. Species identification was by matrix-assisted laser desorption ionization-time time of flight mass spectrometry (MALDI-TOF MS). Molecular typing was performed by pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST). Antimicrobial susceptibility was assessed by gradient-diffusion and carriage of bla genes was detected by PCR. Plasmid typing, conjugation assays, S1-PFGE studies and long-read sequencing were used to characterize resistance plasmids. Results: From July 2018 to February 2019, 125 KPC-producing Enterobacterales were recovered from 101 inpatients from surveillance (74.4%) or clinical samples (25.6%), in a tertiary hospital in Barcelona. Clonality studies identified a major clone of Klebsiella pneumoniae belonging to sequence type ST15 and additional isolates of K. pneumoniae, Escherichia. coli and Enterobacter sp. from different STs. All isolates but one carried the blaKPC-2 allelic variant. The blaKPC-2 gene was located in an IncFIIk plasmid of circa 106 Kb in a non-classical Tn4401 element designated NTEKPC-pMC-2-1. Whole-genome sequencing revealed different rearrangements of the 106 Kb plasmid while the NTEKPC-pMC-2-1 module was highly conserved. Conclusion: We report a hospital outbreak caused by the clonal dissemination of KPC-producing ST15 K. pneumoniae but also the intra- and inter-species transmission of the blaKPC-2 gene associated with plasmid conjugation and/or transposon dissemination. To our knowledge, this is the first report of an outbreak caused by KPC-producing Enterobacterales isolated from human patients in Catalonia and highlights the relevance of surveillance studies in the early detection and control of antibiotic resistant high-risk clones.